Coping Strategies and Their Influencing Factors Among Nursing Student in Online Learning - Muhamad Gustaf Al Fajar; Nita Fitria; Sukma Senjaya; Putri Karisa (Poltekkes Kemenkes Semarang, 2023)
Background: the challenge of success for nursing students is getting tougher with the implementation of online learning during the COVID-19 pandemic because it requires adjustments to learning methods that can cause stressors for students.Objective: this study aims to identify a description of the coping strategies used by students of the Faculty of Nursing, Universitas Padjadjaran in carrying out online lectures and the factors that influence them.Methods: this research was a cross sectional design. The population in this study was students of the Faculty of Nursing, Universitas Padjadjaran with a total sample of 271 students who were selected based on the proportional stratified random sampling technique. The instrument used is The Brief COPE questionnaire with 28 statement items,and questionnaire on factors that affect coping strategies with 40 statement items, then analyzed descriptively.Results: the results of the study showed that almost all respondents, namely 208 students (76.75%) had problem focused coping coping strategies. Problem solving skills are the highest factor in the use of coping strategies with a mean value of 0.8413 and physical health being the lowest factor with a mean value of 0.3210.Conclusion: further research is needed with the correlation method to be able to see the factors that influence the use of coping strategies.